Was bringt Religion Öffentlichkeit?: Gesellschaftliche Pluralität als Motiv praktisch-theologischen Nachdenkens - Merle, Kristin (Zeitschrift für Theologie und Kirche, 2021)
The relationship between religion and the public sphere remains precarious. Starting from a problematization of the term »Öffentlichkeitsauftrag der Kirchen«, we are able to consider the conditions for publicly relevant church speech and action whose signature is a societal plurality that the process of deep mediatization accelerates. This results in impulses for a practical theology which is plurality-competent and takes into account the public sphere and public theory.